2005
DOI: 10.1093/ptj/85.8.791
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Neuromuscular Training to Improve Neuromuscular Function and Biomechanics in a Patient With Quiescent Juvenile Rheumatoid Arthritis

Abstract: Background and Purpose. The purpose of this case report is to describe a novel multidisciplinary approach for evaluating and preparing a patient with quiescent juvenile rheumatoid arthritis (JRA) for safe sports participation. Case Description. The patient was a 10-year-old girl with a history of bilateral knee arthritis who desired to participate in soccer and basketball. Range of motion and manual muscle testing of the lower extremity were within normal limits. Neuromuscular testing included kinematic and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…However, it has to be mentioned that it could also be that injured athletes could improve their jump agility less due to the training loss because of the injury; a fact that cannot be neglected based on the present results. Nevertheless, the trainability of neuromuscular control is highest in preadolescent athletes [31] and neuromuscular training can have a preventative effect in reducing the risk of lower extremity injuries [32][33][34]. Therefore, neuromuscular training and testing including agility aspects should be incorporated regularly in the athletic-specific development of youth ski racers.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has to be mentioned that it could also be that injured athletes could improve their jump agility less due to the training loss because of the injury; a fact that cannot be neglected based on the present results. Nevertheless, the trainability of neuromuscular control is highest in preadolescent athletes [31] and neuromuscular training can have a preventative effect in reducing the risk of lower extremity injuries [32][33][34]. Therefore, neuromuscular training and testing including agility aspects should be incorporated regularly in the athletic-specific development of youth ski racers.…”
Section: Discussionmentioning
confidence: 99%
“…If not addressed, neuromuscular deficits may continue into adulthood and increase an athlete's risk for ACL injury . There is clear evidence that neuromuscular training programs can enhance athletic performance through increased strength, power and coordination as well as address neuromuscular deficits . We have demonstrated that it is possible to induce a neuromuscular spurt and improve neuromuscular deficits in females with training .…”
Section: Prevention Techniquesmentioning
confidence: 90%
“…Fortunately, evidence from our laboratory demonstrates that a neuromuscular spurt can be induced in females with neuromuscular training programs. Neuromuscular and biomechanical ACL injury risk factors such as poor landing mechanics, inadequate force attenuation abilities and inefficient muscle recruitment can be modified and neuromuscular training programs that target improvements in strength, power and coordination appear to reduce the risk of ACL injury …”
Section: Establish the Etiology And Modifiable Mechanisms Of Acl Injumentioning
confidence: 99%
See 2 more Smart Citations